Evaluation of Digital Branding Strategy in OJS-Based Journals to Increase Dissemination of Scientific Publications - Marviola Hardini; Mardiana Mardiana; Dwi Andayani; Eka Dian Astuti; Isabella Maria (ADI Journal on Recent Innovation (AJRI), 2026)
The increasing competition among scientific journals requires effective digital branding strategies to enhance publication dissemination and journal visibility. This study aims to evaluate the implementation of digital branding in the ADIMAS Journal using the Electronic Word of Mouth (e-WOM) framework. A descriptive qualitative approach was employed through website observation, social media analysis, documentation, and evaluation based on five e-WOM indicators article sharing, user generated content, author testimonials, academic community, and research collaboration. The findings indicate that ADIMAS (ADI Pengabdian Kepada Masyarakat Jurnal) has established a strong digital presence through Open Journal Systems (OJS), website optimization, and metadata management. However, user engagement, social media interaction, and collaborative promotion remain limited, reducing the effectiveness of publication dissemination. The evaluation demonstrates that integrating e-WOM practices with digital branding can strengthen journal credibility, improve online visibility, and expand the dissemination of scientific publications. This study contributes by providing an integrated evaluation framework that combines digital branding and e-WOM to support sustainable journal development and broader academic communication.